Analysis of Translation Technique Used in Translating a Poetry titled “Alone” by Edgar Allan Poe on Channel YouTube “MDV Translation” - Efriyani, Mira; Inayah, Ratih; Syaputri, Wuri; Widyasari, Widyasari (Puitika, 2025)
This study aims to identify the translation techniques used in translating Edgar Allan Poe's poem "Alone." The MDV Translation’s YouTube channel’s translation of the poetry ‘Alone’ served as the primary source for this research. The researcher conducted this research by comprehensively analyzing documents to identify the types of translation techniques used. For this study, a descriptive qualitative methodology was adopted. Six categories of translation techniques have been found in this study, namely transposition (16.1%), modulation (35.5%), literal translation (19.4%), adaptation (12.9%), reduction (12.9%), and amplification (3.2%). From the data gathered, modulation is one of the most common techniques employed in poetry translation.